2022
DOI: 10.1111/cns.13830
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum occludin after successful reperfusion Is associated with early neurological deterioration

Abstract: Aims Early neurological deterioration (END) is an important factor that affects prognosis in patients with acute ischemic stroke. We explored the relationship between serum occludin levels after successful reperfusion and END in patients treated with endovascular thrombectomy (EVT). Methods We prospectively enrolled 120 stroke patients who underwent EVT with successful reperfusion. Enzyme‐linked immunosorbent assay was used to detect the serum occludin levels on admission and within 1 h after successful reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Moreover, blood-based biomarkers are also found to be predictive for unfavorable early (END) and long-term functional outcomes of EVT-treated AIS patients, including interleukin-6, NLR, N-terminal probrain natriuretic peptide, albumin, matrix metalloprotease-9, enascin-c, thioredoxin, ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13, and occludin, etc. ( 2 , 3 , 10 , 31 35 ). We have recently reported that high levels of the pro-resolving protein mediator annexin A1 correlated with 3-month clinical outcomes of AIS patients who underwent successful recanalization by EVT ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, blood-based biomarkers are also found to be predictive for unfavorable early (END) and long-term functional outcomes of EVT-treated AIS patients, including interleukin-6, NLR, N-terminal probrain natriuretic peptide, albumin, matrix metalloprotease-9, enascin-c, thioredoxin, ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13, and occludin, etc. ( 2 , 3 , 10 , 31 35 ). We have recently reported that high levels of the pro-resolving protein mediator annexin A1 correlated with 3-month clinical outcomes of AIS patients who underwent successful recanalization by EVT ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have adjusted many confounding factors and performed various sensitivity analyses, we were unable to adjust some potential confounders such as dietary magnesium intake status and intensive care unit duration. In addition, recent studies reported some novel prognostic biomarkers associated with stroke outcomes, such as the middle cerebral artery pulsatility index, 65 serum occludin levels, 66 direct bilirubin, 67 and stress-induced hyperglycemia. 68 serum magnesium on poor outcomes of stroke, which could provide more valuable information to understand the mechanism of the associations.…”
Section: Discussionmentioning
confidence: 99%
“…As a component of the blood–brain barrier tight junction protein, serum occludin is also considered one of the biomarkers to predict the prognosis of stroke. A previous study suggested that the elevation of serum occludin is important to judge the damage to the blood–brain barrier in ischemic stroke 52 . Elevated serum occludin levels at baseline were associated with a higher risk of hemorrhage transformation regardless of whether patients received reperfusion therapy, and it might be an independent risk factor for early neurological deterioration in patients receiving endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study suggested that the elevation of serum occludin is important to judge the damage to the blood-brain barrier in ischemic stroke. 52 Elevated serum occludin levels at baseline were associated with a higher risk of hemorrhage transformation regardless of whether patients received reperfusion therapy, and it might be an independent risk factor for early neurological deterioration in patients receiving endovascular thrombectomy. Furthermore, the application value of circulating microRNAs as biomarkers in the diagnosis and prognosis of ischemic and hemorrhagic stroke has also been hotly discussed.…”
Section: Ta B L E 1 Baseline Characteristics Of Enrolled Patients Acc...mentioning
confidence: 95%